Neuroimaging Characteristics of Pruritus Induced by Eczema: An fMRI Study - Tae‐eun Kim; Jin Li; Larissa Tao; Ji‐ming Tao; Xiang‐yu Wei (Brain and Behavior)
ABSTRACT Objective To explore the neuroimaging characteristics of eczema‐induced pruritus with resting‐state functional magnetic resonance imaging (rs‐fMRI). Methods A total of 42 patients with eczema were recruited in the PE group, and 42 healthy participants were included in the HC group. The Visual Analogue Score (VAS), 12‐Item Pruritus Severity Scale (12‐PSS), Pittsburgh Sleep Quality Index (PSQI), and Self‐Rating Anxiety Scale (SAS) were recorded in the PE group. The different values of fraction amplitude of low‐frequency fluctuation (fALFF) and functional connectivity (FC) were compared after rs‐fMRI scanning. Results Compared with the HC group, the fALFF values of the left precentral gyrus, left postcentral gyrus, left supplementary motor area (SMA), and left midcingulate cortex in the PE group were increased. The FC values between the left precentral gyrus, bilateral superior temporal gyrus, bilateral hippocampus, and left inferior occipital gyrus in the PE group were decreased. The FC values between left SMA and bilateral superior temporal gyrus in the PE group were decreased. The 12‐PSS score was positively correlated with fALFF value of the left precentral gyrus and left postcentral gyrus. Conclusion Pruritus caused increased spontaneous activity in given cerebral regions, involving the perception of itch, control of scratching movements, and expression of itch‐related emotions. Meanwhile, there is a correlation between fALFF values of given cerebral regions and clinical scales, which provided potential neurobiological markers for the future study of pruritus.